The mediating roles of environmental values and risk propensity in linking theory of planned behavior and entrepreneurial self efficiency to global sustainable ventures - Syed Khusro Chishty (Discover Sustainability)
Abstract This study investigates how the Theory of Planned Behavior (TPB) constructs—attitudes, subjective norms, and perceived behavioral control influence entrepreneurial intentions in the context of sustainable start-ups in Saudi Arabia. Data were collected from 270 potential entrepreneurs and analyzed using partial least squares structural equation modeling (PLS-SEM) via Smart-PLS software. The findings indicate that attitudes enhance entrepreneurial self-efficacy and environmental values, positively affecting sustainable entrepreneurial intentions. Additionally, subjective norms significantly influence environmental values and sustainable entrepreneurial intentions. Similarly, perceived behavioral control increases risk propensity and environmental values, which in turn fosters sustainable entrepreneurial intentions. These mediating effects underscore the importance of environmental values, and risk propensity in shaping sustainability-driven entrepreneurship. The study contributes to the TPB framework by integrating sustainability and recommends that Filippelli (Bus Strateg Dev 210:123900, 2025) policymakers develop training programs to strengthen entrepreneurial self-efficacy and environmental awareness among aspiring entrepreneurs (Oliveira in 8:e70083, 2025), educational institutions incorporate sustainability-focused entrepreneurship programs to reinforce environmental values, and Christodoulou (Environ Responsib: BusEthics 34:936-950, 2024) financial and mentorship support systems be tailored to mitigate perceived risks, thereby encouraging sustainable venture creation. These targeted interventions can effectively promote sustainable business ventures in Saudi Arabia and similar contexts.